The Effect OF Teacher's Professional Competence on Student’s Entrepreneurship Competency in Practice and Entrepreneurship Lessons at SMKN 1 Solok - Reflin, Pasya Mutia; Fauziyah, Azizah; Nurfitriya, Mira (A Social Science and Entrepreneurship Journal, 2023)
The purpose of this study was to determine the effect of teacher professional competence on student entrepreneurship competence in the subjects of craft and entrepreneurship at SMKN 1 Solok, in this study using a quantitative approach, the data sources used in this study were primary data and secondary data, primary data namely data which is directly obtained from respondents from filling out google forms , while secondary data comes from literature studies in the form of journals, books and laws related to research. The result of the research is that the professional competence of teachers has a positive effect on the entrepreneurial competence of students at SMKN 1 Solok.